Incidence and Predictors of Synchronous Bone Metastasis in Newly Diagnosed Differentiated Thyroid Cancer: A Real-World Population-Based Study - Qi, Lin; Zhang, Wenchao; Ren, Xiaolei; Xu, Ruiling; Liu, Chaoqian; Tu, Chao; Li, Zhihong (Frontiers in Surgery, 2022)
Background: Clinical and sociodemographic characteristics of differentiated thyroid cancer (DTC) patients with synchronous bone metastasis (SBM) remain unclear. This real-world study aimed to elucidate the incidence and prognosis of DTC patients with SBM using population-based data. Methods: Data of patients with newly diagnosed DTC from 2010 to 2016 were retrieved from Surveillance, Epidemiology, and End Results (SEER) database. Multivariable logistic regression analysis was utilized to identify predictors of developing SBM in DTC patients and was further evaluated by receiver operator characteristics (ROC) analysis. Multivariable Cox regression was applied to identify prognostic factors associated with overall survival (OS) and cancer-specific survival (CSS). Results: A total of 67176 patients with DTC were screened from the database, with 0.36% (244/67176) developing SBM. The age-adjusted incidence of SBM in DTC patients was relatively stable during study period with an average annual percentage change (AAPC) of 2.52. Multivariable logistic regression analysis recognized seven factors (older age, male gender, black race, other races, follicular histology, AJCC T2, T3, T4 staging and N1 staging) as predictors of developing SBM among the entire cohort, with the value of area under the curve (AUC) of 0.931 (95%CI: 0.915 to 0.947). Median survival time of DTC patients with SBM was 22 months (interquartile range, 7-47 months). The Multivariable Cox regression analysis indicated multiple metastatic sites, surgical procedures and chemotherapy as predictors for survival of patients. Conclusions: Predictors and prognostic factors of SBM in DTC patients were identified in this study. Patients with risk factors should be given more attention in clinical practice.